Ide Kreatif Iklan Audio Visual Pariwisata Paniis Lestari - Altobeli Lobodally; Satya Candrasari (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2022)
Paniis Lestari as a tourism driving community in Paniis Village has a number problems in promoting Paniis as a tourism village. The lack of promotion is one of the problems that need to be solved, in addition to the tsunami disaster that hit the area. For this reason, community service communities are carried out to formulate audio-visual product concept for the promotion of Paniis. In this activity, community service offers the ASDAMBA concept for Paniis Lestari. What, Who, Where Why and How. What can be done in Paniis, who can be contected to go to Paniis, where is Paniis, why do we have to go to Paniis, and how do we go to Paniis. The concept then produces a work product than can be uploaded to Paniis Lestari’s social media.